E-cigarette side effects in otolaryngology: unveiling the vape mirage - Gabriele Baniulyte (17885981) (2023)
Data sources The following databases were searched for publications up to May 2020: Web of Science, EMBASE, CENTRAL, Medline and CINAHL. Additionally, previously published reviews were hand searched. Study selection Clinical studies conducted in English language were considered, encompassing cohorts of more than four vaping individuals who have encountered inadvertent side effects. Both adult and paediatric populations were included. In vitro, animal studies and systematic or literature reviews were excluded from the analysis. Data extraction and synthesis Two independent reviewers screened 1125 studies following deduplication. Two-hundred and eight full-text studies were assessed for eligibility. Results Thirty-two studies met the inclusion criteria. Diverse study designs were included, comprising of cross-sectional, randomised controlled trials, case-control studies, cohort studies, case series investigations and non-randomised trials. Of note, four studies focused on paediatric patients. Most reported side effects were cough, throat and mouth irritation and intra-oral lesions. Conclusions While the direct side effects of e-cigarettes are well-documented, the long-term effects remain uncertain. Other Information Published in: Evidence-Based Dentistry License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41432-023-00941-0